(3GdchGcH GdOQjI aj Gdafhf GdCOHjIs - (3MSjf Hf eMeO Hf eUWaj GdMSf,J (B1327 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdHOjY HjGfg , GdeWdb Mceg hSdWGfg CeG HYO , ajbhd deG hLOJ ai gPG GdReGf QZHI dENhGffG GdWdHI ai GdYdhe GdCOHjI NUhUkG Yde GdHOjY CQOJ Cf CLeY cJGHkG ai GdYdhe GdKdGKI hSejJg s
(3BNQgG (B:s
(3heeG jQTOc dYdh eQJHI GdJgPjH VQH GdeKd HMhdjGJ RgjQ Hf CHj Sdei , hJbOje YeQ Hf GdNWGH dg Ydi SGFQ GdaMhd ef WdbJg heeG bjd ajg jfSH dGHf Ydi GdefLe GfXQ JLeO UhQ GdCTYGQ hGMOI hEfeG deYGf JYTb GdUhQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eDWQI HGdCMeQs
(3cJHJ GdYfGhjjf hGdahGJM HGdMeQI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B258s
Keywords: (3GdCOHs